Design Principle and Development Trends of Silicon-Based Anode Binders for Lithium-ion Batteries: A Mini Review (Journal of Solar Energy Research Updates, 2024)
Abstract: Silicon (Si), recognized as a promising alternative material for the anodes of lithium-ion batteries, boasts a high theoretical specific capacity and abundant natural availability. During the preparation of silicon-based anodes, binders play a pivotal role in ensuring the cohesion of silicon particles, conductive agents, and current collectors. The structure and performance of these binders are critical for the mechanical stability, electrical conductivity, and stress dissipation capacity of the anodes. This review initially outlines the structural characteristics of various binders, including linear, branched, and three-dimensional cross-linked types. It then delves into the relationship between the structure and properties of these binders in the context of their application in high-performance lithium-ion batteries, focusing on their mechanical properties, electrical conductivity, and self-healing capabilities. Particular attention is given to the design strategies for binders that facilitate stress dissipation, with an emphasis on integrating multifunctional polymer binders renowned for their superior conductive and self-healing features. Such binders contribute to the formation of a robust three-dimensional network structure via multiple bonding mechanisms, including chemical, non-covalent, and coordination interactions. This configuration significantly enhances the adhesion between silicon particles, thereby facilitating the efficient dissipation of stress, which is a key aspect for ensuring the long-term cycling stability of lithium-ion batteries. Lastly, the paper explores future development directions for silicon anode binders, advocating for a thorough investigation into the synergy of diverse structural and functional combinations, with the aim of advancing the performance and practical application of silicon-based lithium-ion batteries.